THE EFFECT OF SOURSOP LEAF DECOCTION WASH (ANNONA MURICATA) ON THE INCIDENCE OF VAGINAL DISCHARGE IN ADOLESCENT GIRLS: IMPLICATIONS FOR MIDWIFERY EDUCATION AND REPRODUCTIVE HEALTH PROMOTION - Izki Millah Nafisah; Rosyidah Alfitri; Anik Sri Purwanti (EDUCATIONE, 2025)
Adolescent girls are especially susceptible to reproductive tract infections, including pathological vaginal discharge (leucorrhea), which can negatively affect their quality of life and academic performance. While pharmacological treatments exist, their use may be constrained by side effects, cost, antibiotic resistance, and limited access in low-resource settings. Herbal remedies such as soursop (Annona muricata) leaf decoction are gaining recognition for their antimicrobial and antifungal benefits, but experimental evidence among Indonesian adolescents remains scarce. This study evaluated the effectiveness of soursop leaf decoction wash in reducing pathological vaginal discharge among tenth-grade female students at SMA An-Nur Bululawang, Malang. A pre-experimental, one-group pretest-posttest design was used with 25 purposively selected participants. The intervention involved a soursop leaf decoction wash administered twice daily for seven days. Vaginal discharge status was assessed before and after intervention using validated questionnaires and observation sheets. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. After the intervention, there was a significant reduction in both the incidence and severity of pathological vaginal discharge. Prior to treatment, 56% had mild discharge, while post-intervention, 96% had no discharge. The mean discharge score dropped from 1.88 (SD = 0.83) to 1.04 (SD = 0.20), with statistical significance (p = 0.000). Soursop leaf decoction wash proved to be an effective, safe, and culturally accepted intervention to reduce pathological vaginal discharge in adolescent girls. This suggests its potential as a complementary or alternative therapy alongside conventional treatments. Integrating herbal interventions with reproductive health education in schools can empower adolescents with accessible, preventive options. Further research with larger, randomized samples and longer follow-up is recommended to confirm efficacy and safety.